Differential expressions of apoptotic genes in lung (A549) cancer cells established by treatment with senna italica extracts - Moloantoa, Malose Ivan (My University, 2021)
Lung cancer is the most diagnosed cancer with an estimated 3 million deaths expected by 2035. Bioactive phytochemicals present in plants are preferred as anticancer therapeutic agents, due to their ability to differentiate between cancerous and normal cells. One such plant, Senna italica, is traditionally used to treat diabetes, malaria, constipation, jaundice, fever and sexually transmitted diseases. Several studies have reported on its anti-proliferative potential against different types of cancers. However, there is scanty information regarding its molecular mechanism of action against different types of cancers, more especially lung cancer. This study, therefore, aims to determine the differential expression profiles of apoptotic genes in lung A549 cancer cells induced by treatment with S. italica leaf and root extracts in an attempt to understand its purported anticancer molecular mechanism of action. The leaves and roots of S. italica were dried in the dark and extracted with ethyl acetate and methanol. Screening for the presence of secondary metabolites was performed using thin layer chromatography and various standard chemical-based tests. The total phenolic and flavonoid compounds were evaluated using gallic acid and quercetin equivalence assays. The antioxidant activity of S. italica extracts was determined using DPPH free radical scavenging and ferric ion reducing power assays. The cytotoxicity of both leaf and root extracts on lung A549 cancer cells was evaluated using 3-(4,5- dimethylthiazol-2-yl)-2-5-diphenyl tetrazolium bromide (MTT) and further confirmed by Muse cell count and cell viability assays. The proliferation of cells, after treatment with different concentrations of the extracts, was examined using the Ki67 proliferation assay. Genotoxicity was determined to assess the potential damage caused by the extracts on the DNA using a MUSETM multicolour DNA damage kit following manufacturer’s protocol. The morphological change of cells treated with different concentrations of S. italica ethyl acetate root extract was analysed using acridine orange/ ethidium bromide (AO/EB) dual staining assay and examined under fluorescent light. The total number of cells undergoing apoptosis was also determined using the Annexin V assay. The expression of 84 key genes, involved in programmed cell death or apoptosis, was determined using the Human Apoptosis RT² Profiler PCR array kit. Senna italica methanol extract had a high content of plant materials in both leaves and roots compared to the ethyl acetate extract. A higher phenolic content was observedxii mainly in the leaf extract and a higher flavonoid content was observed in the root extract. Phytochemicals, such as phenols, tannins, flavonoids, terpenoids and steroids, which are known to exhibit anti-cancer activity against cancerous cells were abundant in the ethyl acetate leaf and root extracts as compared to the methanol leaf and root extracts. Additionally, the ethyl acetate root extract exhibited more antioxidants and radical scavenging activity in comparison to the methanol root extract. The IC50 of ethyl acetate root extract was determined to be 200µg/ml. Both methanol and ethyl acetate root extracts had little to no effect on the viability of lung A549 lung cancer cells. The results were confirmed by cell count and viability assay results. The cytotoxicity of ethyl acetate root extract was also evaluated against the normal kidney HEK-293 cells, which displayed little cytotoxic effect. The proliferation results indicated that S. italica ethyl acetate root extract has the potential to reduce the proliferation of lung A549 cancer cells. The ethyl acetate root extract was found to induce late apoptosis in A549 cells, but the genotoxicity data indicated that the DNA double strand breaks (DSBs) were repairable. The results further showed an expression of different genes that inhibit apoptosis, such as XIAP in lung A549 cells, following treatment with S. italica ethyl acetate root extract. In conclusion, the ethyl acetate root extract displayed a promising anti-cancer therapeutic potential, and thus warrants further investigation to elucidate the identity of the inherent chemical components that are responsible for the observed biological activity.
Thesis (M.Sc. (Biochemistry)) -- University of Limpopo, 2021
Keywords: Lung cancer; Apoptotic genes; Cancer cells; Senna Italica extracts; Lungs -- Cancer